Character Education with Islamic Insights of The Nusantara - Siti Yumnah (Nazhruna: Jurnal Pendidikan Islam, 2021)
The emergence of the idea of ​​character education programs in Indonesia is understandable. This is because so far the community has judged that the education process has not succeeded in nurturing Indonesians. For this reason, it is necessary to strengthen the values ​​of national character education, combining Islamic religious values ​​with an archipelago perspective, or commonly called character education based on Nusantara Islam. The Nusantara Islamic philosophy is considered very suitable for character education for the Indonesian nation. This paper uses a qualitative research approach using library research methods. Using the library method to collect data, namely collecting data in the form of text that supports this research. Based on the results of the study, it can be concluded that Nusanatara Islam is an Islam based on cultural infrastructure. Then the concept of character education based on Islam Nusantara is pesantren, madrasa, Integrated Islamic school, university and tradition or culture. Islam Nusantara has many character education values, including obedience, independence, simplicity, togetherness, the spirit of gotong royong, compassion, equality, deliberation, moderation (tawasut}) and tolerance (tasamuh).